2021
DOI: 10.20535/2410-8286.214627
|View full text |Cite
|
Sign up to set email alerts
|

Developing Intercultural Business Competence via Team Learning in Post-Pandemic Era

Abstract: To become successfully competitive in the globalised post-COVID 19 virtual business world, the engineering students, besides learning the English language for Specific Purposes as stipulated by the existing Syllabi, require purposed efforts for the formation of intercultural business communication competencies. This research, conducted successively in the USA and Ukraine combining observational and experimental methodology, aimed at studying the influence of team learning on the development of intercultural bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Although programs and courses may utilize adult learning principles, few studies assess the impact in health services disciplines [11]. Andrienko et al (2021) showed that team-based learning (TBL) has a positive effect on outcomes related to adult learning in undergraduate higher education, such as business communication, global employment, and intercultural competence [56]. Two-team simulations are efficient and effective [62].…”
Section: Meeting Needs Of Age Cognitive Styles or Developmental Phase...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although programs and courses may utilize adult learning principles, few studies assess the impact in health services disciplines [11]. Andrienko et al (2021) showed that team-based learning (TBL) has a positive effect on outcomes related to adult learning in undergraduate higher education, such as business communication, global employment, and intercultural competence [56]. Two-team simulations are efficient and effective [62].…”
Section: Meeting Needs Of Age Cognitive Styles or Developmental Phase...mentioning
confidence: 99%
“…The research team identified several articles that not only focus on the training and implementation of team-based learning in a real-world environment to achieve better patient and/or organizational outcomes, but also aim to grow and support a safety culture [27,56,57]. Implementing team-based learning in the health services workplace can significantly enhance safety standards and practices.…”
Section: Organizational Leadership Team-based Learning/collaborationmentioning
confidence: 99%
“…Firstly, scientists justify the need for such training in the modern world (Andrienko et al, 2021;Freeman et al, 2022;Soulsby et al, 2021).…”
Section: Introductionmentioning
confidence: 99%